Serum progesterone concentration on day of embryo transfer in donor oocyte cycles - Brady, Paula C. (Springer US, 2014)
PURPOSE: To evaluate the association between serum progesterone (P) levels on the day of embryo transfer (ET) and pregnancy rates in fresh donor IVF/ICSI cycles. METHODS: Fresh donor cycles with day 3 ET from 10/2007 to 8/2012 were included (n = 229). Most cycles (93 %) were programmed with a gonadotropin releasing hormone (GnRH) agonist; oral, vaginal or transdermal estradiol was used for endometrial priming, and intramuscular P was used for luteal support (50–100 mg/day). Recipient P levels were measured at ET, and P dose was increased by 50–100 % if <20 ng/mL per clinic practice. The main outcome measure was rate of live birth (> = 24 weeks gestational age). Generalized estimating equations were used to account for multiple cycles from the same recipient, adjusted a priori for recipient and donor age. RESULTS: Mean recipient serum P at ET was 25.5 ± 10.1 ng/mL. Recipients with P < 20 ng/mL at ET, despite P dose increases after ET, were less likely to achieve clinical pregnancy (RR = 0.75, 95 % CI = 0.60–0.94, p = 0.01) and live birth (RR = 0.77, 95 % CI = 0.60–0.98, p = 0.04), as compared to those with P ≥ 20 ng/mL. P dose increases were more often required in overweight and obese recipients. CONCLUSIONS: Serum P levels on the day of ET in fresh donor IVF/ICSI cycles were positively correlated with clinical pregnancy and live birth rates. An increase in P dose after ET was insufficient to rescue pregnancy rates. Overweight and obese recipients may require higher initial doses of P supplementation. Future research is needed to define optimal serum P at ET and the interventions to achieve this target.